A glimpse on the contributions and challenges towards more environmentally-friendly road traffic - Macedo, Eloísa (2022)
Managing a complex system such as a road transport network, is not easy and requires efficient Operational Research procedures. In this context, modelling and simulation play a key role for planning, managing and anticipate impacts by testing different scenarios. New emerging technologies and ever-increasing level of automated in-vehicle functions are expected to provide benefits in terms of reducing pollutant emissions, increasing road safety, and reducing travel costs. But will there be only benefits? Although connected and automated vehicles (CAVs) are not fully deployed yet in the roads (only pilot cases are running in some major cities around the world), the truth is that there will be a long period of CAVs sharing the roads with conventional vehicles (CVs). Recently, much attention has been devoted to studying and exploring the impacts of a mixed road traffic environment. In this chapter, we review several interesting studies on the advances in transport systems with sustainability concerns, mainly focused on CAVs context.